Coğrafya Öğretmenlerinin Teknolojik Pedagojik Alan Bilgisi İle İlgili Yeterliliklerinin İncelenmesi / Examining the Skills of Geography Teachers’ Technological Pedagogical Content Knowledge - Doğru, Esengül; Aydın, Fatih (Journal of History Culture and Art Research, 2017)
Abstract The main purpose of this research was to determine the competencies of technological pedagogical content knowledge (TPCK) of geography teachers and to examine whether these competencies differed significantly according to various variables. The study included a total of a total of 42 geography teachers employed in Karabuk city centre and its districts in 20015-2015 education year. The data of the study was gathered though Technological Pedagogical Content Knowledge (TPCK) developed by Pamuk, Ergun, Çakır, Yılmaz ve Ayas (2012). Frequency and percentage values along with Kolmogorov-Smirnov (K-S) test, Mann Whitney U test and Kruskal Wallis H test were used to analyse the data of the current study. The results of the study revealed that the technological pedagogical content knowledge of geography teachers was not enough. Results also demonstrated the level of geography teachers’ technological pedagogical content knowledge did not differ significantly according to their skills and knowledge at using technology, seniority, education level and gender. Content Knowledge is one of the subscales of TPCK that geography teachers had the highest level of knowledge. Furthermore, the level of technological content knowledge of geography teachers was higher than that of technological pedagogical knowledge. The results of the study were discussed in line with the related literature and some suggestions were made. Öz Bu araştırmanın temel amacı, Coğrafya öğretmenlerinin Teknolojik Pedagojik Alan Bilgisi (TPAB) yeterliliklerinin tespit edilmesi ve bu yeterliliklerin çeşitli değişkenlere göre farklılık gösterip göstermediğinin incelenmesidir. Çalışmaya, 2015-2016 eğitim öğretim yılında Karabük il merkezi ve ilçelerinde görev yapmakta olan toplam 42 Coğrafya öğretmeni katılmıştır. Veri toplama aracı olarak, araştırmanın nicel kısmı için ölçme aracı olarak Pamuk, Ergun, Çakır, Yılmaz ve Ayas (2012) tarafından geliştirilen, Teknolojik Pedagojik Alan Bilgisi (TPAB) ölçeği kullanılmıştır. Verilerin analizinde yüzde ve frekans değerleri, Kolmogorov-Smirnov (K-S) testi, Mann Whitney U testi, Kruskal Wallis H testi kullanılmıştır. Araştırma sonuçları, Coğrafya öğretmenlerinin Teknoloji Bilgilerinin (TB) yeterli olmadığını göstermektedir. Coğrafya öğretmenlerinin Pedagojik Bilgileri (PB), teknolojiyi kullanmadaki bilgi ve becerilerine, meslekteki hizmet yıllarına, eğitim durumlarına ve cinsiyetlerine göre farklılaşmadığı sonucuna ulaşılmıştır. TPAB’nin alt boyutlarından olan Alan Bilgisi (AB), öğretmenlerin en yüksek seviyede bilgi sahibi oldukları boyuttur. Ayrıca öğretmenlerin, Teknolojik Alan Bilgisi (TAB) düzeylerinin Teknolojik Pedagojik Bilgi (TPB) düzeylerine göre yüksek çıktığı görülmüştür. Araştırma sonuçları ilgili alan yazınla ilişkili bir biçimde tartışılmış ve bazı öneriler sunulmuştur.